Analysis Of Regional Inequality in Gorontalo Province 2015-2022 - Shela Oktadiani; Fahrudin Zain Olilingo; Herwin Mopangga; Sri Endang Saleh (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Efforts to reduce regional inequality and shift regional inequality are important in all countries. This study aims to determine the level of regional inequality, shifts in district/city regional inequality and the relationship between economic growth, investment and government spending with regional inequality in Gorontalo Province in 2015-2022. The data used in this study are sourced from the Central Bureau of Statistics of Gorontalo Province. Data analysis tools used Williamson Index Analysis, Klassen Typology Index Analysis and Quantitative Descriptive. The results showed that (1) the average level of regional inequality that occurred in Gorontalo Province in 2015-2022 was 0.16, which means that the level of regional inequality that occurred was low. (2) From the results of the Klassen Typology analysis in Gorontalo Province in 2015 and 2022 where there are four regions that are left behind, namely regions that have a lower growth rate and per capita income than Gorontalo Province. Boalemo Regency, Bone Bolango Regency, Gorontalo Regency and North Gorontalo Regency and there is one developed but depressed area that has a higher per capita income rate, but its economic growth rate is lower than Gorontalo Province, namely Pohuwato Regency which is accompanied by a developed and rapidly developing area that has a higher economic growth rate and per capita income than Gorontalo Province, namely Gorontalo City. (3) The average increase in economic growth fluctuated by 4.85 percent. This means that the increase in economic growth during 2015-2022 can reduce regional imbalances that occur in Gorontalo Province. (4) The average increase in investment amounted to 1,187.23 billion rupiah. This shows that an increase in investment during 2015-2022 can reduce regional inequality in Gorontalo Province. (5) Average increase in government expenditure amounted to 5,820,736.38 million rupiah.